Front-loading Urban Stormwater Management for Success – A Perspective Incorporating Current Studies on the Implementation of Retrofit Low-impact Development - Matthew A. Morrison; William D. Shuster; Rachel Webb (Cities and the Environment, 2008)
Recent work into the implementation of low-impact development (LID) suggests that a decentralized, source-control approach has the potential to significantly reduce urban stormwater runoff quantity. The practice of retrofit stormwater management is currently dominated by demonstration projects, and some additional momentum is required to spur upscaling of LID practices so that the scale of this management approach can better match the scale of disturbance, and furthermore broaden adoption of these practices. This momentum may be provided in part by targeted research into effectiveness of stormwater best management practices insofar as research accounts for cost and effectiveness (e.g., water quality benefits, and actual stormwater capture) under a variety of climate conditions. We posit that the factors of increasing public participation in stormwater management; engaging local agencies and non-governmental organizations (NGOs); application of proven source control methods to mitigate runoff formation; and science-based, comprehensive monitoring strategies are all important to the sustainable implementation of retrofit low-impact development. From the perspective of federal researchers and local NGOs, this paper presents features, objectives, and costs of recent efforts to properly scale demonstration projects and broader LID initiatives. In order to realize the full benefits of decentralized LID stormwater management practices in urban and suburban areas, we conclude that a nexus must exist of a motivated and engaged citizenry, solid support from municipal and regional agencies, sound source control management practices, and follow-up monitoring to judge effectiveness.